Jaringan Islamisasi Gorontalo (Fenomena Keagamaan dan Perkembangan Islam di Gorontalo) - Mashadi Mashadi; Wahidah Suryani (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
In this article, the authors argue that Gorontalo Municipality, which is believed to have been founded as the centre of government since 1728 AD, or precisely in 6 Sya'ban 1140 H., has become an